Palladium-Catalyzed C6-Selective C–H Acylation of 2-Pyridones - Chen, Zhiwei; Zhang, Lei; Zhao, Danxia; Hu, Gangao; Yu, Chuanming (Synlett, 2020)
2-pyridonesC6-selectivepalladium catalysisC–H acylationradicalA versatile palladium-catalyzed C6-selective C–H acylation of 2-pyridones with commercially available aldehydes using TBHP as an oxidant has been developed. This protocol tolerated diverse functional groups and has excellent level of site selectivity. Moreover, it does not require silver salts as additives.